Ereth's birthday - Avi, 1937-; Floca, Brian (New York : HarperTrophy, 2001)
Feeling neglected on his birthday, Ereth, the cantankerous old porcupine, sets out looking for his favorite treat and instead finds himself acting as "mother" to three young fox kits.
Five Owls.
Publisher's Weekly.
School Library Journal.
4.8.
4.8
3-6
Keywords: Animals -- Fiction; Foxes -- Fiction; Parent and child -- Fiction; Porcupines -- Fiction; Animals -- Fiction; Foxes -- Fiction; Parent-child relationship -- Fiction; Porcupines -- Fiction